Controllability of Second Order Stochastic Impulsive Differential Equations in Hilbert Spaces - 李美丽 田峻钢 李毓媛 (东华大学学报（英文版）, 2016)
The exact controllability of second order stochastic impulsive differential equations in Hilbert spaces is studied.By using the Holder＇s inequality,stochastic analysis and fixed point strategy,some sufficient conditions are given,but no compactness condition is imposed on the cosine family of operators.This work improves some previous results without impulses or stochastic factors.